2023
DOI: 10.31234/osf.io/tz6x2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards formal models of inhibitory mechanisms involved in motor imagery: A commentary on Bach et al. (2022)

Abstract: A vast body of research suggests that the primary motor cortex is involved during motor imagery. This raises the issue of inhibition: Given the role of the motor system in providing the multisensory content of motor imagery, how is it possible for motor imagery not to lead to motor execution? Bach et al. (2022, this issue) suggest that the motor execution threshold may be “upregulated” during motor imagery to prevent execution. Alternatively, it has been proposed that, in parallel to excitatory mechanisms, inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Regarding the first mechanism, Bach et al (2021) suggested that the motor (execution) threshold may be "upregulated" during motor imagery to prevent execution. How this would be achieved or implemented however, is not specified (Nalborczyk et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the first mechanism, Bach et al (2021) suggested that the motor (execution) threshold may be "upregulated" during motor imagery to prevent execution. How this would be achieved or implemented however, is not specified (Nalborczyk et al, 2023).…”
Section: Discussionmentioning
confidence: 99%